2021
DOI: 10.1021/acs.est.1c03042
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of In-Use NOx Emissions from Heavy-Duty Diesel Vehicles Equipped with Selective Catalytic Reduction Systems

Abstract: This work evaluated the nitrogen oxide (NOx) emissions of 277 heavy-duty diesel vehicles (HDDVs) from three portable emission measurement system testing programs. HDDVs in these programs were properly maintained before emission testing, so the malfunction indicator lamp (MIL) was not illuminated. NOx emissions of some HDDVs were significantly higher than the certification standard even during hot operations where exhaust temperature was ideal for selective catalytic reduction to reduce NOx. For engines certifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In addition, we listed the measurement results of Europe and the United States in Table S2. The measured NO X EFs of in-use HDTs were much higher than their counterparts in Europe and the United States. It was found that the BC emission levels were merely comparable to those of the U.S. fleets tested in 2009–2011 and considerably higher than those in the United States after 2013 . This is due to the high emitters contributing considerably to the total emissions.…”
Section: Resultsmentioning
confidence: 93%
“…In addition, we listed the measurement results of Europe and the United States in Table S2. The measured NO X EFs of in-use HDTs were much higher than their counterparts in Europe and the United States. It was found that the BC emission levels were merely comparable to those of the U.S. fleets tested in 2009–2011 and considerably higher than those in the United States after 2013 . This is due to the high emitters contributing considerably to the total emissions.…”
Section: Resultsmentioning
confidence: 93%
“…However, the fact that we observe high NO x emissions in the newest HDV at all of the sites, an observation also reported by other researchers, suggests an issue that involves more than temperature differences. 42 There are no significant differences between Utah (7.19 ± 0.97 gNO x /kg of fuel) and Cottonwood, CA (7.5 ± 4.5 gNO x / kg of fuel) means for the newest vehicles, though Cottonwood uncertainties are very large. The Cottonwood measurements are different in that the higher means are not the result of a larger number of high-emission outliers but an increase in emissions between the 25th and 85th percentiles (Figure S12).…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…This is consistent with the hypothesis that lower ambient temperatures have lowered the SCR conversion efficiency (Figure S1) rather than increased the number of catalysts that are inoperative. However, the fact that we observe high NO x emissions in the newest HDV at all of the sites, an observation also reported by other researchers, suggests an issue that involves more than temperature differences …”
Section: Results and Discussionmentioning
confidence: 99%
“…Regarding ISNOx emissions, the F NOx is 0.46 to equalize the median merit function values with the fuel consumption. This consideration is done because the intended vehicle for the current engine is required to have a selective catalytic reduction destined to reduce this pollutant (these aftertreatment devices can have relatively high efficiency if the exhaust temperatures surpass a minimum threshold 4244 ), although due to the differences of NOx reduction capabilities between laboratory tests and real-world use 45 the lowest value for this emissions is preferable.…”
Section: Resultsmentioning
confidence: 99%